Platelet receptors: fibrinogen - Plow, Edward F.; Haas, Thomas A.; Byzova, Tatiana V. (Platelets in Thrombotic and Non-Thrombotic Disorders, 2002)
Introduction and historic perspectivesScientists have always been intrigued by the highly visible reactions. Hence, platelet aggregation and fibrin deposition, the key events in one of the most visually dramatic of biological reactions, thrombus formation, have been the subject of intensive scrutiny for many decades. Evidence for an interplay between these key components of the thrombus had already begun to evolve in the early 1960s. Platelets in plasma derived from patients with afibrinogenemia failed to aggregate or aggregated poorly when stimulated with ADP or epinephrine, but a robust aggregation response occurred upon addition of fibrinogen to the plasma. These observations also were documented in artificially defibrinated and reconstituted plasma. In the 1970s, as investigators became adept at isolating functional platelets, the role of fibrinogen in platelet aggregation was corroborated; and the requirements for an agonist, a divalent cation and fibrinogen to support the aggregation response was documented. By the late 1970s, formal studies, utilizing approaches developed to examine hormone–receptor interactions, to measure the direct interaction of fibrinogen with platelets, were under way. Thus, in the early 1980s, results from multiple laboratories had documented that platelets expressed fibrinogen receptors, capable of binding this plasma protein in a specific and saturable manner. Furthermore, an important functional response, platelet aggregation, could be ascribed to the binding of fibrinogen to the platelet surface.